STUDI TENTANG FAKTOR-FAKTOR PENYEBAB PERNIKAHAN SEMARGA DI DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Magdalena Claudya Nahampun; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the occurrence of cases of clan marriages of the Toba Batak tribe in Duri such as couples who marry in the same clan even though clan marriages are prohibited by custom, in this case the Toba Batak customs, customary provisions have been violated by the Toba Batak indigenous people themselves, Couples who are married in the same clan are no longer ashamed and are no longer awkward to show their existence. This clan marriage is prohibited, both by custom and by church, for example the HKBP and Catholic Churches. This clan marriage occurred not only in the Batak Toba Perantuan community but also in the place of origin of the Toba Batak tribe, namely in North Sumatra. The purpose of this study was to determine the factors that led to marriage within the same clan in Duri, Mandau District, Bengkalis Regency. In this study, researchers used qualitative methods and data collection techniques that researchers did were observation, interviews, and documentation. This research carried out in Duri, Mandau District, Bengkalis Regency, in this study researchers used interviews and observations as primary data and documentation as secondary data, data analysis used in this study were data collection, data reduction, data presentation, and drawing conclusions. The informants in this study were traditional leaders, church leaders, married couples and youths. Based on the results of the study, it was found that the factors that caused clan marriages in Duri could occur due to economic factors, religious/church factors, education factors, love factors, and overseas factors. Of the five factors, the love factor and the economic factor are the factors that have the most potential to cause family marriages for couples from Batak Toba in Duri, Mandau District, Bengkalis Regency.Key Words: Factors, Causes, Marriage, The Same Clan